Comparison of Brain-Behavioral Systems, Decision Making Styles and Cognitive Emotion Regulation in Adults with and without ADHD - Asiyeh Vakia; Reza Soltani Shal; Abbas Abolghasemi (روانشناسی بالینی و شخصیت)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) in adults can have numerous negative consequences for both the individual and society. Consequently, it is essential to identify the factors associated with this disorder.The aim of the present study was to compare behavioral brain systems, decision-making processes, and cognitive emotion regulation in adults with and without ADHD. Method: The research design employed a causal-comparative approach. The population for this study consisted of students at the University of Guilan, from which a sample of 320 individuals was selected through convenience sampling. This sample included 120 students exhibiting symptoms and 200 students without symptoms. The research tools utilized in this study included the World Health Organization Adult Attention Deficit Hyperactivity Disorder Self-Rating Scale (ASRS), the Brain/Behavioral Systems Questionnaire (BAS-BIS), the General Decision-Making Styles Questionnaire (GDMS), and the Short Form of the Cognitive Emotion Regulation Questionnaire (CERQ). The research data were analyzed using univariate and multivariate analysis of variance with SPSS version 16 software.Results: The results indicated that there was no significant difference in the activation system and behavioral inhibition system between adults with ADHD and those without. However, a significant difference was observed between the two groups regarding the rational, intuitive, dependent, impulsive, and avoidant components of cognitive decision-making.Additionally, maladaptive emotion regulation strategies were more prevalent in adults with ADHD compared to those without the condition; however, adaptive emotion regulation strategies were found to be equally utilized by both groups.Discussion and conclusion: The findings of this study provide evidence for the psychopathology of Attention Deficit Hyperactivity Disorder (ADHD) in adults and highlight the role of cognitive variables in this disorder.These findings indicate that decision-making styles and cognitive emotion regulation are among the variables that influence adult ADHD. Consequently, psychological training can be employed to modify these characteristics, as well as to address adult ADHD.